Sanitary standards in the EU: the impact of Malaysian fishing industry - Alavi, Rokiah (SESRIC, 2009)
Malaysia seafod exports to EU faced blanket ban in 2008. The European union is known to have the most stringent regulations with regard to food safety and standards. This has caused significant impact on fisheries industry in Malaysia because the EU is the principal export market for the Malaysian seafood products and the fisheries sector is the second most important foriegn exchange earner of the country. This industry employ about 10,000 workforce who are directly involved in this industry in additon to 50,000 others who are indirectly employed in the sector.